Views of the Swiss public towards gene editing - Kelly E. Ormond; Sara Kijewski; Naomi Wyler; Agata Ferretti; Eirini Petrou; Claudia Reichmuth; Effy Vayena (PLoS ONE, 2026)
There is little country-specific data about how the general public views gene editing therapies. In Autumn 2023 we randomly surveyed the Swiss public, using the Federal Register and stratifying by language region (German, French, Italian), gender and age. We present a representative sample of 3855 responses, including >4000 open-ended comments. When presented with 7 therapeutic options for somatic gene editing, 7% disagreed with all therapeutic options, and 35% supported them all. Most agreed with using somatic gene editing to cure life-threatening (76%) and debilitating diseases (70%); support declined as severity decreased or with later onset. Few supported somatic gene editing to enhance physical (6%) or cognitive (9%) abilities. In all scenarios, people were less likely to agree with gene editing of embryos. Notably, all therapeutic gene editing attitudes clustered, regardless of somatic vs. germline differentiations. Factor analysis also demonstrated two clusters for “support” and “caution” towards gene editing, and multivariate analysis demonstrated relationships with age, gender, religion and knowledge. When asked what influenced their views, the most endorsed reasons for feeling positively were ‘views towards what it means to have a good life’ (59.8%) and ‘views about illness and suffering’ (58.5%). Most selected “neutral” to describe religion’s influence (68.9%) despite findings that those who endorsed high religiosity were less supportive and more cautious towards gene editing. Conclusions: Uncovering systematic differences in the attitudes towards specific therapies and the values shaping them underscores the importance of including peoples’ voices in policy decisions in a country-specific manner.